Taking Space to Grow Food and Community: Urban Agriculture and Guerrilla Gardening in Vancouver - Black, Rachel (Cuizine)

(untitled) (McGill University Library, 2013)
City planners and citizens often see gardens as spaces for urban beautification projects. However, urban agriculture and growing food in cities is becoming an increasingly accepted use of public green spaces. This article examines how gardeners and the City of Vancouver negotiate space while trying to create green cities, greater awareness of food security issues, and community in urban environments. These gardens show how local discourses of health, environment, and food production are created through this process of appropriating urban spaces for horticultural activities. Based on ethnographic fieldwork, this paper explores the development of spontaneous and grassroots urban agriculture movements in Vancouver. This research was carried out from 2006 to 2008 while the city was preparing for the 2010 Winter Olympic Games. At this time, Vancouverites, local officials, and Games organizers were concerned about putting on a “green” Games. As the media spotlight began to fall on Vancouver, urban agriculture became a very public demonstration of the city’s environmental awareness. This article looks at how, at a particular historic moment, grassroots gardening movements gained mainstream acceptance and played a role in constructing the city’s image as an environmentally aware urban place with a high standard of living.